2012
DOI: 10.1111/j.1365-2141.2011.09022.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction and its role in haematological cancer

Abstract: SummaryObservations in human tumours, as well as mouse models, have indicated that telomere dysfunction may be a key event driving genomic instability and disease progression in many solid tumour types. In this scenario, telomere shortening ultimately results in telomere dysfunction, fusion and genomic instability, creating the large-scale rearrangements that are characteristic of these tumours. It is now becoming apparent that this paradigm may also apply to haematological malignancies; indeed these condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 124 publications
(169 reference statements)
1
39
0
3
Order By: Relevance
“…The evidence that telomere erosion/telomere fusion causes genome instability in cancer is generally indirect, such as shortened telomeres or the presence of anaphase bridges [Rudolph et al, 2001;Gordon et al, 2003;Letsolo et al, 2010;Jones et al, 2012]. Capper et al [2007] showed that the presence of fewer than 13 telomere hexanucleotide repeats at the end of a chromosome is not sufficient to form a functional, non-fusogenic telomere.…”
Section: Telomere Fusionmentioning
confidence: 99%
“…The evidence that telomere erosion/telomere fusion causes genome instability in cancer is generally indirect, such as shortened telomeres or the presence of anaphase bridges [Rudolph et al, 2001;Gordon et al, 2003;Letsolo et al, 2010;Jones et al, 2012]. Capper et al [2007] showed that the presence of fewer than 13 telomere hexanucleotide repeats at the end of a chromosome is not sufficient to form a functional, non-fusogenic telomere.…”
Section: Telomere Fusionmentioning
confidence: 99%
“…Short and dysfunctional telomeres limit normal stem cell proliferation and lead to genomic instability, predisposing both to hematologic malignancies and solid tumors (7,8). In hematopoietic cancers, associations between telomere length, disease progression, and prognosis have been noted (8,9). We aimed to investigate the roles and the interactions of TERT rs2736100 and JAK2 rs12343867 (tagging 46/1 haplotype) polymorphisms in Hungarian BCR-ABL1-negative MPN, CML, and AML patients concerning their frequencies and potential effects on clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, TL and telomerase expression may constitute prognostic tools and potential targets for anticancer drugs. 12 This concept, first established in solid tumors, 13,14 can now be applied in most hematologic malignancies. 15,16 Relatively few studies on telomere status and telomerase activity (TA) in T-cell malignancies have been published.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Relatively few studies on telomere status and telomerase activity (TA) in T-cell malignancies have been published. 12,17 The aim of this study was to investigate such parameters in cutaneous T-cell lymphomas (CTCLs), since they were not previously assessed in neoplastic cells. [18][19][20] We focused on common subtypes of CTCL: 2 aggressive forms, transformed mycosis fungoides (T-MF) and Sézary syndrome (SS) with a median survival of ;2 years, and primary cutaneous anaplastic large cell lymphoma (C-ALCL), with a favorable prognosis (10-year disease-related survival exceeding 90%).…”
Section: Introductionmentioning
confidence: 99%